Clinical Outcomes of Ileostomy Closure before Adjuvant Chemotherapy after Rectal Cancer Surgery: An Observational Study from a Chinese Center - Zhen Sun; Yufeng Zhao; Lu Liu; Jichao Qin (Gastroenterology Research and Practice)
Background. The optimal timing of temporary ileostomy closure with respect to the time of adjuvant chemotherapy following sphincter-saving surgery for rectal cancer remains unclear. The aim of this study is to investigate the clinical and oncological outcomes of ileostomy closure before, during, and after adjuvant chemotherapy following curative rectal cancer resection. Methods. Patients diagnosed with rectal adenocarcinoma who underwent low anterior resection and temporary loop ileostomy during May 2015 and September 2019 were retrospectively evaluated. Patients undergoing ileostomy closure before adjuvant chemotherapy (Group I) were compared to patients undergoing closure during (Group II) and after (Group III) adjuvant chemotherapy. Results. A total of 225 patients were evaluated for eligibility, and 132 were finally selected and divided into 3 groups (24 in Group I, 53 in Group II, and 55 in Group III). No significant differences were observed in operative time, postoperative hospital stay, postoperative complications, total adjuvant chemotherapy cycles, and low anterior resection syndrome scores among the three groups. There was no significant difference in disease-free survival (p=0.834) and overall survival (p=0.462) between the three groups. Conclusion. Temporary ileostomy closure before adjuvant chemotherapy following curative rectal cancer resection can achieve a clinical and oncological safety level equal to stoma closure during or after chemotherapy in selected patients.